European Muslims and the Qur’an: practices of translation, interpretation and commodification - Sibgatullina, Gulnaz Rifkhatovna; Wiegers, Gerard Albert (The European Qurʾan, 2024)
"This edited volume aims to advance a Muslim-centered perspective on the study of Islam in Europe. To do so, it brings together a range of case studies that illustrate how European Muslims engaged with their Sacred Scripture while being part of a Christian-dominated social and political space. The research presented in this volume seeks to analyse Muslims' practices of translating, interpreting and using the Qur'an as a sacred object and, thus, pursues three main research agendas. Part I focuses on the issues of Muslim-Christian relations in Europe and studies how these relations have engendered discursive connections between Muslim- and Christian-produced texts related to the study and interpretation of the Qur'an. Part II aims to bring scholarly attention to the under-represented cases of Muslim communities in Europe. This part introduces new research on Polish-Belarusian, Daghestani, Bosnian and Kazan Tatars and examines local traditions of producing vernacular Qur'ans and commodification of Qur'anic manuscripts. The final section of the volume, Part III, contributes to filling in the gaps related to the theoretical and conceptual framing of Muslim translation activities. The history of religious thought and practice in European history is in many ways still uncharted territory. This book aims to contribute to a better understanding of the cultural history of the Qur'an and Muslim agency in interpreting, transmitting and translating the Sacred Scripture."--